The Concept of Private Property Rights in Civil Law - Allambergenova Zamira Rasbergen qizi (Scientific Trends, 2024)
In this article, the concept of private property rights in civil law, the reforms carried out in the field of private property rights and the adopted legal documents, the scientists who conducted research on private property and their opinions, the provisions of foreign countries' laws on private property rights, private property advantages over other types of property, basic concepts of subjects and objects of private property rights are described.
Keywords: Property, private property, property protection, private property objects, private property subjects.